ON COMPATIBILITY OF HIGHER EDUCATION AND MENTAL RETARDATION - Samokhin, Ivan; Sergeeva1, Marina; Nikashina, Natalia; Nagornova, Ekaterina; Shaleeva, Elena (Revista Inclusiones, 2020)
Inclusive education is a very broad concept. According to the World Health Organization, there are about a billion people with disabilities having completely different diagnoses – from cerebral palsy to hyperactivity, from blindness to schizophrenia, from asthma to Down syndrome. Therefore, a general discussion about inclusive education is hardly possible. It is required to discuss if not a specific disease, then at least a group, type of disorders, which can be divided into physical, emotional and mental. People with mental retardation (Down syndrome, cretinism, hydrocephalus, etc.) form a special group, concerning which it seems a priority to discuss not the methods of inclusion, but its expediency. This topic is very polemical within primary and secondary education. Many people think that an ordinary teacher cannot work with mentally challenged children, since he/she is not able to use special methods and techniques. There is, however, an opposite opinion, which is officially approved by the Federal Law “On Education in the Russian Federation”. Complex spiritual needs and sophisticated social ones are not available to mentally challenged people, hence their path to happiness is not very winding. However, happiness will become unattainable if such persons are involved in the higher education system (provided that it is called higher in the traditional sense, which is not completely lost).